2000
DOI: 10.1023/a:1011980313237
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Orthotopic implantation of a metastatic cell line of Lewis lung carcinoma (LLC-MLN), which was isolated by an in vivo selection method, resulted in greater metastatic growth in mediastinal lymph nodes as compared with that of the original LLC cells. LLC-MLN cells also had increased invasive ability and activator protein-1 (AP-1) transcriptional activity as compared with the original LLC cells. This is well consistent with the previously reported finding that overexpression of AP-1 is associated with lymphatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…1). This is highly consistent with our previous observation in mediastinal lymph node metastases of orthotopically implanted Lewis lung carcinoma cells, in which curcumin inhibited the metastasis but not the primary tumor growth [16]. These results suggest that curcumin targeted metastasis-specific processes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1). This is highly consistent with our previous observation in mediastinal lymph node metastases of orthotopically implanted Lewis lung carcinoma cells, in which curcumin inhibited the metastasis but not the primary tumor growth [16]. These results suggest that curcumin targeted metastasis-specific processes.…”
Section: Discussionsupporting
confidence: 93%
“…Curcumin, a natural product of the Indian spice turmeric isolated from Curcuma longa , has potent anti-inflammatory [12], anti-carcinogenic [13]and anti-metastatic [14, 15, 16]activities. It has been shown that the suppression of AP-1 transcriptional activity is one major part of the activities of curcumin [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that 24 to 30-hr treatments reduced the number of cells in a dose-dependent manner, which is in agreement with published results using other cell lines 1 as well as LLC 37. However, a shorter treatment interval (2 or 4 hrs) significantly reduced the density of cells only when they were treated with the highest curcumin dose (60 µM).…”
Section: Discussionsupporting
confidence: 90%
“…We selected a well studied lung cancer cell line to evaluate the use of curcumin at concentrations that are known to be cytotoxic to many different cancer cells 36. Previously, when LLC cells were used in an orthotopic tumor model, with the cells implanted in the lungs, curcumin administered orally had no effect on tumor growth but did minimize metastasis to lymph nodes near the lungs 37, suggesting that curcumin or its metabolites had some effects despite low bioavailability following ingestion.…”
Section: Discussionmentioning
confidence: 99%